Total electrolyte balance for laying hens - Silva,Vitor Colossal da (2021)
ABSTRACT: This study was done to determine the best value of the total electrolyte balance (BET) concerning the variables of performance and egg quality of the laying hens. We investigated 240 Hy-Line Brown laying hens, of 30 to 46 weeks of age, adopting the completely randomized experimental design, which included five treatments (1000, 1250, 1500, 1750 and 2000 μeq / kg), 8 repetitions and 6 birds per unit. The performance and quality of the birds’ eggs were evaluated in the different treatments. The results were subjected to the analysis of variance and, wherever significant effect was noted, the regression equations were estimated, taking into account the electrolyte balance (μeq / kg) as a concomitant variable, applying the SAS statistical program (2001). The consumption, production, and feed conversion variables by dozen eggs, final bird weight, egg density, yolk color, Haugh Unit, albumen weight, shell weight, and egg weight, were found to be unaffected by the experimental BET values. The values of the feed conversion per egg mass, yolk weight and uniformity were affected by the different BETs. The electrolyte balance values showing minimum feed conversion, higher yolk weight, and better uniformity were, respectively, BET = 1400, 1330, and 1250 in μeq / kg of loads at the different temperatures. From the regression equations, the value indicated was BET=1390 for the 30- to 46-week-old laying hens. The electrolyte balance of the diet was found to affect the laying hens in terms of performance and egg quality.